Public Health and Economic Resilience in Morocco: Towards a Sustainable Healthcare Model - NASSOU, Yousra (International Journal of Scientific Research and Innovative Studies, 2025)
This article explores the interconnections between public health and economic resilience in Morocco, with a particular focus on the country’s efforts to develop a sustainable healthcare model. Drawing on recent reforms, investment strategies, and the lessons of the COVID-19 pandemic, the study examines how health expenditures, institutional frameworks, and innovation in medical services contribute to long-term economic stability. The analysis highlights three key dynamics: (i) the macroeconomic implications of healthcare financing, (ii) the role of public–private partnerships in expanding medical infrastructure, and (iii) the integration of sustainability principles in health policies. The paper argues that Morocco’s ability to align healthcare reform with economic diversification strategies will determine its resilience in the face of future shocks. The article adopts a theoretical and policy-oriented approach, combining insights from economic literature, health economics, and international reports. Findings underline that investment in healthcare is not merely a social priority but also a strategic economic lever for sustainable development. Available Online at https://www.ijsrisjournal.com/index.php/ojsfiles/article/view/460 Received Date: December 18, 2024 Accepted Date: January 12, 2025 Published Date: February 01, 2025